Pregão eletrônico e seu impacto na melhoria do gasto público - Vila Nova, Andréa Maria Porto Câmara (2011)
The purpose of this study is to analyze a comparison in Ceará State Government Purchase Politics in a period before trading and during it (in the years of 1999 and 2009, respectively). To compare trading efficiency and others licitation modalities it was used data of acquired properties of the same nature. Regression statistical analysis was used. The proposed model analyzed three variables: acquisition price, time of process permanency and number of participants. It was verified that acquisition price and time of process permanency are not statically relevant, and that the number of participants has a significant relation to acquisition price, indicating that the licitation modality does not represent a determinant factor of efficiency.